ANALYSIS OF CORPORATE SOCIAL RESPONSIBILITY IN FINANCIAL PERFORMANCE (CASE STUDY OF AIRASIA MALAYSIA) - Nanda Arif Wicaksana; Estu Widarwati; Nunik Nurmalasari (DIMENSIA (Diskursus Ilmu Manajemen STIESA), 2020)
This study aims to explain the role of corporate social responsibility (CSR) on the financial performance of a case study of the airline company Airasia Berhad This research data collection method is a literature study, and researchers obtain information from Airasia Berhad's annual report. based on the results of this study CSR has an important role on financial performance with the reputation and achievements of companies that care about the environment to be more value for stakeholders in considering buying company shares so that it has an impact on rising company stock prices.